Long Term Follow-up Data and Health-Related Quality of Life in Frontline Therapy of Fit Patients Treated With FCR Versus BR (CLL10 Trial of the GCLLSG) - Nadine Kutsch; Jasmin Bahlo; Sandra Robrecht; Jeremy Franklin; Can Zhang; Christian Maurer; Nisha De Silva; Elisabeth Lange; Rudolf Weide; Michael G. Kiehl; Martin Sökler; Rudolf Schlag; et al. (HemaSphere, 2020)
Abstract. Fludarabine, cyclophosphamide and rituximab (FCR) was compared to bendamustine and rituximab (BR) in an international, randomized, open label, phase 3 trial in 561 previously untreated, fit patients with chronic lymphocytic leukemia (CLL) without del (17p). Primary endpoint was progression free survival (PFS). The final primary endpoint analysis after 37.1 months median follow up failed to show the non-inferiority of BR as compared with FCR. With extended median follow up of 58.2 months, median PFS was 42.3 months in BR-treated patients versus 57.6 months for FCR-treated patients (Hazard Ratio [HR] 1.593; 95% CI 1.271–1.996; p < 0.0001). For patients > 65 years, median PFS was 48.5 months with BR versus 57.9 months with FCR without reaching statistical significance (HR 1.352; 95% CI 0.912–2.006; p = 0.134). Median OS was not reached for both arms with 5-year OS rates of 80.1% vs 80.9%, respectively (HR 1.108; 95% CI 0.755–1.627; p = 0.599). No statistically significant difference was found in the time to secondary malignancy between the 2 groups (at 5 years, 86.6% free from secondary malignancies in the BR group vs 83.8% in the FCR group [HR 0.801; 95% CI 0.507–1.267; p = 0.344]). In patients >65 years secondary neoplasia occurred more frequently after FCR treatment [28 of 86 (32.6%) patients] as compared with BR [18 of 107 (16.8%) patients; p = 0.011]. Health-related quality of life was similar in both treatments. Despite the improved PFS for FCR, OS did not differ. These results also suggest an increase in secondary neoplasia associated with FCR in elderly fit CLL patients.